G391(P) Use of non-invasive respiratory support in bronchiolitis: a national survey. (27th April 2015) - Turnham, H; Agbeko, R; Furness, J; Sutcliffe, A; Ramnarayan, P
Abstract : Aims: Bronchiolitis accounts for a significant proportion of hospital and intensive care admissions in children aged <1 year. 1, 2 Nasal continuous positive airway pressure (nCPAP) has been used traditionally as first-line respiratory support modality. Heated-humidified High Flow Nasal Cannula (HFNC) therapy is rapidly gaining popularity as an alternate mode of non-invasive respiratory support due to its ease of use. This is despite lack of clinical trial evidence to support its use in bronchiolitis. 3 We aimed to establish current practice relating to HFNC and CPAP use in the United Kingdom (UK). Methods: We devised an on-line survey (Survey Monkey, USA) and disseminated the link through regional retrieval services to hospitals with paediatric inpatient facilities. Responses were requested from one senior nurse and doctor from each hospital. The questionnaire covered: hospital characteristics, clinical indications for use of CPAP and/or HFNC in bronchiolitis, and willingness to participate in future research. Denominator data (number of UK hospitals with inpatient services) was obtained from the RCPCH 2013 census. Results: Five regional retrieval services distributed the survey to their local hospitals, covering 109 of 191 hospitals in the UK with inpatient paediatric services. 156 respondents from 102 individual hospitals provided information (response rate: 94%). Of the 102 hospitals, 23 had a dedicated paediatric intensive care unit, 38 a dedicated paediatric high dependency unit (PHDU), 50 had dedicated PHDU beds on general paediatric wards. 30% have no PHDU provision. 95 (93%) units can deliver nCPAP to children with bronchiolitis and 73 (71%) can deliver HFNC. The main indications for HFNC use: as an alternative to nCPAP (69%), escalation of therapy from low flow oxygen (74%), and weaning from nCPAP (57%). The majority (71%) would choose HFNC over nCPAP in a deteriorating child with bronchiolitis; despite this, 76% were prepared to randomise infants between nCPAP and HFNC in a clinical trial. Conclusions: Use of HFNC is common across UK hospitals. Despite this, survey responses support clinical equipoise amongst the majority of clinicians, indicating the feasibility of a trial of nCPAP and HFNC at this time. References: Nagakumar P, Doull I. Current therapy for bronchiolitis. Arch Dis Child. 2012;97(9):827–830 Paediatric Intensive Care Audit Network, 2013 Annual Report. Accessed June 2012 Beggs S, Wong ZH, Kaul S, Ogden KJ, Walters JA. High flow nasal canula therapy for infants with bronchiolitis. Cochrane Database Syst Rev 2014:CD009609